Navigating generational shifts: a study on enhancing parental self-efficacy in 21st-century Indian families - Singh, Shivangi (My University, 2024)
Over 20% of the world’s children are born in India, where rapid societal change challenges traditional parenting values. This pilot study, grounded in a behavioural science framework, tested a brief, culturally tailored online counselling intervention targeting parental self-efficacy, parenting behaviour, mental health, and child adjustment. Sixty-seven urban, middle-class, English-speaking parents of children aged 6–14 years were randomised to intervention or control groups. The intervention drew on Bandura’s principles of verbal persuasion, social comparison, and mastery experience to generate behavioural insights. Outcomes were assessed two weeks post-intervention using structural equation modelling (SEM). No significant effects were observed, but the study demonstrates the feasibility of applying experimental, quantitatively driven methods in this context. Findings highlight the need to refine intervention components and further examine self-efficacy within Indian families.
The International Society for the Study of Behavioural Development (ISSBD) Conference
PRESENTED
Lisbon, Portugal
Keywords: self-efficacy; parenting behaviour; child adjustment; Indian parents; single-session; pilot; Identities in Transformation; International Development; Child centred research questions, study design, data analysis; Childhood Self-Esteem; Mental health promotion